Trainee teacher’s interest and motivation towards teaching and teaching practicum performance: a case study in Faculty of Education, UiTM Seksyen 17 / Nurul Fathiha Ibrahim - Ibrahim, Nurul Fathiha (Faculty of Education, 2014)
A genuine interest in teaching among the trainee teachers assists them to excel during the practicum as they enjoyed the teaching process, Ogonor and Badmus (2006, p.5). Meanwhile, Guajardo (2011, p.3), stated that the more basic needs (extrinsic motivation) and environmental factors are adequately met, the teachers become more motivated to perform in schools.This case study aimed to identify the trainee teacher’s interest and motivation before, during and after teaching practicum. This study also sought to find out the reason(s) the trainee teacher joined B. Ed Hons (TESL) programme in Faculty of Education, UiTM Seksyen 17. This study involved a trainee teacher who had completed her teaching practicum and currently in last semester of the programme in Faculty of Education, UiTM Seksyen 17. In gathering the data regarding the trainee teacher’s interest and motivation, qualitative data was adopted in analysing entries of the journal and interview transcription. Apart from that, coding was used in categorising the identified themes in both instruments. The findings revealed that the trainee teacher developed her situational interest and extrinsic motivation once she joined the teaching programme and at the beginning of the teaching practicum. The result also indicated the trainee teacher had fully developed her individual interest and intrinsic motivation once she had completed her teaching practicum.